Faunistic analysis of Acridomorpha (Orthoptera: Acridoidea and Eumastacoidea) in São Sepé, RS, Brazil - LEAL DE CARVALHO, NATHÁLIA; CORRÊA-COSTA, ERVANDIL; BOANERGES-SOUZA, DANILO; GARLET, JULIANA (Revista Colombiana de Entomología, 2012)
The research aimed to characterize the community of Acridomorphs through faunal analysis, and to determine the ideal sample size for studies with this group, in two areas from municipality of São Sepé, RS, Brazil. The specimens were collected by sweep netting, travelling distances of 5, 10, 15, 20 and 25 m, in order to determine which would be the best distance for collecting of acridomorphs. The collections were done between January and May 2009. The calculation of the values of diversity indexes was assessed using the Simpson dominance (D), Shannon-Wiener diversity (H), Margalef richness, and equitability (J’). Data were analyzed by a nonparametric free distribution chi-square test. The collected material represented 947 acridid and 20 proscopids distributed in two superfamilies, 12 genera and 23 species. The species that had high levels of significance in area A were: Dichroplus silveiraguidoi, Notopomala glaucipes and, Scotussa cliens, all Acrididae. In area B, eight species showed significant rates Aleuas vitticollis, Amblytropidia sola, Dichroplus conspersus and Dichroplus silveiraguidoi, all Acrididae. In terms of statistical precision, according to the size of a sample to collect, it was 5 m. The best sample size in terms of statistical precision was 5 m for distance traveled. Starting from 25 m, the greatest number of individuals and species diversity was obtained, but showed a high standard deviation and variance. In this way, both size can be recommended for collecting acridomorphs, depending on the purpose of the study.